Diseño de un centro de producción, capacitación y venta de productos agrícolas en la quebrada Corral Viejo de San Antonio de Ibarra - Guevara Amaya, Lesly Dayana (2023)
The expansion-contraction of the rural agricultural territory in San Antonio de Ibarra, province of Imbabura, presents shortcomings in infrastructure, services and opportunities for optimal development of agronomists and their agricultural production, detected through the collection of information from different techniques and methodologies. such as the Agroecosystems methodology of Lorena González in 2020, which is based on the implementation of cartographies and the observation of the environment, this allows knowing three types of categories: habitat, rural environment and rural productivity, as well as surveys based on the INEC 2021 and diagnostic sheets prepared by Sánchez in 2018.. The application of them gave us the result that the production in San Antonio de Ibarra is divided between 11, 046% NAP-1. agricultural production in greenhouse crops and with 88.95% as NAP-2 agricultural production, horticultural and fruit orchards of free exposure. In addition, there is no wholesale market linkage in the sector, which is mandatory in rural areas, complicating the economic income of farmers according to the LOTUGS, as well as promoting technical assistance training and technological innovation to improve the productivity of agricultural crops in rural areas, in the sector there is no center in which such training is carried out. Likewise, only 36% have irrigation water, and the crops in the western zone are the only ones that have this service due to their proximity to the Corral Viejo stream and 64% of the farmers belonging to the zone do not have this service in their crops, and the contamination of the stream was also observed due to the fact that the sewage from the houses flows into the stream without any type of treatment. That is why three interventions are proposed, at a micro level in which the Recovery Production and Sale of Rural Agricultural Products in the Corral Viejo stream is proposed to encourage agricultural production, as well as the regeneration of the same in San Antonio de Ibarra. On a meso scale it is proposed to create recreational spaces in the Corral Viejo stream to encourage the care of the stream and the recreation of all its inhabitants and on a macro scale it is proposed to create a phytoremediation system that helps the improvement of the Corral Viejo stream, generating specific points of improvement in addition to the implementation of irrigation water systems that distribute the water in an equitable manner as well as the design of climatic tiles and channels that will collect rainwater and help with this equitable distribution of irrigation wat